Correlation between fruit weight and nutritional metabolism during development in CPPU-treated Actinidia chinensis ‘Hongyang’ - Qiu, Guo-liang; Zhuang, Qi-guo; Li, Yu-fei; Li, Si-yu; Chen, Cun; Li, Zheng-hao; Zhao, Yu-yang; Yang, Yi; Liu, Zhi-bin (PeerJ, 2020)
Forchlorfenuron, N-(2-chloro-4-pyridyl)-N-phenylurea (CPPU), is often used to promote fruit growth and improve production. The role of CPPU in kiwifruit growth has been established. However, the correlation between fruit weight and nutritional metabolism during development after CPPU treatments remains largely undetermined. Here, we surveyed the variations in weight and nutrient components of the ‘Hongyang’ kiwifruit (Actinidia chinensis) when CPPU was sprayed on fruit 25 days after anthesis. The CPPU application did not significantly influence the dry matter, soluble solids, starch, vitamin C or protein concentrations. However, the fresh weight, length and maximum diameter were significantly increased compared with the control. Moreover, in fruit of the same developmental stage, the fructose, glucose and soluble sugar levels increased after the CPPU treatment, compared with the control. On the contrary, citric, quinic and titratable acid concentrations decreased. However, a correlation analysis between fresh weight and the nutritional contents revealed that CPPU did not affect the concentrations of the most abundant organic acids (quinic and citric) and sugars (glucose, fructose and sucrose), compared with control fruit of the same weight. Therefore, CPPU applications enhance ‘Hongyang’ kiwifruit weight/size. However, there were no significant differences in the nutritional qualities of treated and untreated fruit having the same weights.
Keywords: ‘Hongyang’ kiwifruit; CPPU; Nutritional metabolism; Development process; Correlation analysis